Decentralization estimators for instrumental variable quantile regression models - Hiroaki Kaido; Kaspar Wüthrich (Quantitative Economics, 2021)
The instrumental variable quantile regression (IVQR) model (Chernozhukov and Hansen (2005)) is a popular tool for estimating causal quantile effects with endogenous covariates. However, estimation is complicated by the nonsmoothness and nonconvexity of the IVQR GMM objective function. This paper shows that the IVQR estimation problem can be decomposed into a set of conventional quantile regression subproblems which are convex and can be solved efficiently. This reformulation leads to new identification results and to fast, easy to implement, and tuning-free estimators that do not require the availability of high-level "black box" optimization routines.
Keywords: C21; C26; 330; bootstrap; contraction mapping; fixed-point estimator; Instrumental variables; quantile regression